Anthropometry of Newborn Infants Born in 14 Teaching Centers in Indonesia - Anna Alisjahbana; Alex Chaerulfatah; Ali Usman; Sri Sutresnawati (Indonesian Pediatric Society, 1994)
Percentile curves representing intrauterine growth of Indonesian infants ranging from 34 to 43 weeks of gestation in 14 teaching centers were constructed from birth weight, birth length, and head, mid-upper arm, and chest circumferences. The gestational age was determined based on the last menstrual period. Mothers with probable chronic diseases or pregnancy complications were excluded. Included for analysis were 5844 singleton newborns. The mean birth weight of Indonesian babies was higher for gestational age of 34-38 weeks, but lower at 40-42 weeks of gestation compared with that of the Denver study. The results showed that the mean birth weight of Denver's newborns was significantly different than that of the Indonesian infants, therefore the Denver intrauterine growth curve cannot be used as reference curve for Indonesian newborns. Baby boys in general bad a higher mean birth weight, birth length, head circumference, and chest circumference. No difference was found for arm circumference. For every gestational age and percentiles, later born infants were heavier than first born infants. Birth weight at 42 weeks was lower for first born infants, this was not shown in later-born infants which showed higher weight for each percentiles. Parity affected birth weight more than birth length. Birth length became more stable at 39 weeks. Chest circumference of < 29 em had the highest sensitivit,y and positive predictive value for low birth weight, followed by arm circumference of < 9 cm. The use of intrauterine growth chart in studying the nutritional status of babies at birth was described.